Metodologia para despacho de fontes de GD a biogás em redes de distribuição utilizando lógica fuzzy - Martins, Luiz Fernando Guarenti (2012)
The aim of this work is determine the most appropriated period for connection of a particular generation source fueled by biogas on a distribution network. The biogas is produced through anaerobic reactions that occur in the municipal solid waste deposited at the landfill specific landfill in analysis. The Minas do Leão landfill is taken as study case, predicting the connection of this generation source on a distribution network supported by the State Company of Electrical Energy (CEEE). The Biogas® software was used to estimate the amount of methane generated in the landfill and to determine the landfill life cycle. By using that information it is possible to plot the power electrical generation curve in MW. The choice for the Biogas® software is justified because this tool is free software developed between the federal government environment state administration and the CETESB (Technology Company of Environmental Sanitation of the State of Sao Paulo). After that, the PSL®DMS software was used to simulate the main electrical characteristics of the network in analysis. These simulations provided the data for evaluating the quantitative parameters voltage levels, power losses and load current. A group of decision makers were selected for establishing scores applied to the qualitative parameter evaluation - availability of ancillary services support. After the definition of the quantitative and qualitative parameters a multiobjective methodology was developed. In the first step of the methodology are applied pertinent fuzzy functions trapezoidal variables that consider electrical characteristics of the network and also the voltage levels defined in the PRODIST (Proceedings of Electric Energy Distribution on Electrical National System). The second part is associated with the decision makers estimative, in which the decision maker presents some scores for each type of ancillary service in analysis, according to the specific moment when this ancillary service will be supported. For these evaluations are considered the demand curve of the feeder where the distributed source will be connected. The methodology was then applied for selecting and ranking the most appropriated period to connect the distributed generation source on the distribution network. The definition of the ranking is the outcome of the data evaluation according to the final priorities quantitative and qualitative analysis.